Water Sorption Controls Extreme Single‐Crystal‐to‐Single‐Crystal Molecular Reorganization in Hydrogen Bonded Organic Frameworks. Issue 57 (17th August 2022) - Boer, Stephanie A.; Conte, Luke; Tarzia, Andrew; Huxley, Michael T.; Gardiner, Michael G.; Appadoo, Dominique R. T.; Ennis, Courtney; Doonan, Christian J.; Richardson, Christopher; White, Nicholas G.
Abstract: As hydrogen bonded frameworks are held together by relatively weak interactions, they often form several different frameworks under slightly different synthesis conditions and respond dynamically to stimuli such as heat and vacuum. However, these dynamic restructuring processes are often poorly understood. In this work, three isoreticular hydrogen bonded organic frameworks assembled through charge‐assisted amidinium⋅⋅⋅carboxylate hydrogen bonds (1 C/C, 1 Si/C and 1 Si/Si ) are studied. Three distinct phases for 1 C/C and four for 1 Si/C and 1 Si/Si are fully structurally characterized. The transitions between these phases involve extreme yet recoverable molecular‐level framework reorganization. It is demonstrated that these transformations are related to water content and can be controlled by humidity, and that the non‐porous anhydrous phase of 1 C/C shows reversible water sorption through single crystal to crystal restructuring. This mechanistic insight opens the way for the future use of the inherent dynamism present in hydrogen bonded frameworks. Abstract : Supramolecular frameworks assembled through charge‐assisted hydrogen bonds are shown to undergo extreme molecular restructuring in response to stimuli (heat, vacuum, humidity). This restructuring involves the complete rotation of both building blocks and occurs in a single crystal to single crystal manner resulting in reversible high enthalpy water sorption in a 3D hydrogen bonded framework.